Reorganization of cortical blood flow and transcranial magnetic stimulation maps in human subjects after upper limb amputation. - Kew, J; Ridding, M; Rothwell, J; Passingham, R; Leigh, P; Sooriakumaran, S; Frackowiak, R; Brooks, D (1994)
1. Two complimentary techniques were used to study cortical function in six human upper limb amputees: positron emission tomographic (PET) measurements of regional cerebral blood flow (rCBF) were made in subjects during limb movements to study activation of the primary motor (M1), primary somatosensory (S1), and association cortices; and electromyographic responses to transcranial magnetic stimulation (TMS) were measured in proximal upper limb muscles to assess the excitability of corticospinal neurons in subjects at rest. 2. To explore possible cortical mechanisms governing the phantom limb phenomenon, PET and TMS findings were compared between subjects with acquired, traumatic upper limb amputations (n = 3), in whom phantom limb symptoms were prominent, and congenital upper limb amputees (n = 3) without phantom limbs. 3. Paced shoulder movements were associated with significant blood flow increases in the contralateral M1/S1 cortex of both groups of amputees. In traumatic amputees, these increases were present over a wider area and were of significantly greater magnitude in the partially deafferented cortex contralateral to the amputation. In congenital amputees blood flow increases were also present over a wider area in the partially deafferented M1/S1 cortex, but their magnitude was not significantly different from that in the normally afferented M1/S1 cortex. 4. Abnormal blood flow increases also were present in the partially deafferented M1/S1 cortex of traumatic amputees during movement of the ipsilateral, intact arm. Abnormal ipsilateral M1/S1 responses were not present during movement of the intact arm in the congenital group. 5. TMS studies showed that the abnormal blood flow increases in the partially deafferented M1 cortex of traumatic amputees were associated with increased corticospinal excitability.(ABSTRACT TRUNCATED AT 250 WORDS)